Mechanism of cognate sequence discrimination by the ETS-family transcription factor ETS-1 - Huang, Kenneth (J Biol Chem, 2019)
Functional evidence increasingly implicates low-affinity DNA recognition by transcription factors as a general mechanism for the spatiotemporal control of developmental genes. Although the DNA sequence requirements for affinity are well-defined, the dynamic mechanisms that execute cognate recognition are much less resolved. To address this gap, here we examined ETS1, a paradigm developmental transcription factor, as a model for which cognate discrimination remains enigmatic. Using molecular dynamics simulations, we interrogated the DNA-binding domain of murine ETS1 alone and when bound to high-and low-affinity cognate sites or to nonspecific DNA. The results of our analyses revealed collective backbone and side-chain motions that distinguished cognate versus nonspecific as well as high- versus low-affinity cognate DNA binding. Combined with binding experiments with site-directed ETS1 mutants, the molecular dynamics data disclosed a triad of residues that respond specifically to low-affinity cognate DNA. We found that a DNA-contacting residue (Gln-336) specifically recognizes low-affinity DNA and triggers the loss of a distal salt bridge (Glu-343/Arg-378) via a large side-chain motion that compromises the hydrophobic packing of two core helices. As an intact Glu-343/Arg-378 bridge is the default state in unbound ETS1 and maintained in high-affinity and nonspecific complexes, the low-affinity complex represents a unique conformational adaptation to the suboptimization of developmental enhancers.